Instruments to assess the oral language of children fitted with a cochlear implant: a systematic review - Mariane Perin da Silva; Ademir Antonio Comerlatto Junior; Maria Cecília Bevilacqua; Simone Aparecida Lopes-Herrera (University of São Paulo, 2011)
The oral language development depends on the effective development of the hearing system. In cases of children presenting with hearing loss, a cochlear implant is an electronic device indicated to (re)habilitate the hearing function. Thus, it is of paramount importance to assess and follow the oral language development of children fitted with a cochlear implant (CI) to measure the effectiveness of the electronic device and support the therapeutic planning of these children. Questions are currently being raised about the instruments to assess the oral language of children using a CI, and, seeking the answers, this systematic review aimed at surveying these instruments. Searches were performed in three different databases utilizing six different descriptors to select articles published from 2004 to 2009 that performed an oral language assessment of children with a CI. Initially, 373 articles were found, and, after the application of inclusion criteria, 47 articles were analyzed, resulting in a survey of 74 instruments for oral language assessment, including tests, questionnaires and inventories. In analyzing the articles, it was realized that the studies included in this systematic review presented varied methodologies and low levels of evidence, with a greater concentration of instruments assessing receptive and expressive language, emphasizing the survey of the child's vocabulary and questionnaires. Thus, it can be verified that other linguistic skills, such as morphosyntactic, semantic, and narrative-pragmatic ones that are important in structuring speech and language for the effectiveness of the child's speech, are not being focused on. Just one of the instruments cited, a questionnaire, was specific for the oral language assessment of children with cochlear implants.